Answer:
![\boxed{k = \frac{L^2 + p}{4t}}](https://tex.z-dn.net/?f=%5Cboxed%7Bk%20%3D%20%5Cfrac%7BL%5E2%20%2B%20p%7D%7B4t%7D%7D)
General Formulas and Concepts:
<u>Algebra I</u>
Basic Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify given.</em>
<em />![\displaystyle L = \sqrt{4kt - p}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20L%20%3D%20%5Csqrt%7B4kt%20-%20p%7D)
<u>Step 2: Solve for </u><u><em>k</em></u>
We can use equality properties to help us rewrite the equation to get <em>k</em> as our subject:
Let's first <em>square both sides</em>:
![\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cbegin%7Baligned%7DL%20%3D%20%5Csqrt%7B4kt%20-%20p%7D%20%26%20%5Crightarrow%20L%5E2%20%3D%20%5Cbig%28%20%5Csqrt%7B4kt%20-%20p%7D%20%5Cbig%29%20%5E2%20%5C%5C%26%20%5Crightarrow%20L%5E2%20%3D%204kt%20-%20p%20%5C%5C%5Cend%7Baligned%7D)
Next, <em>add p to both sides</em>:
![\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\& \rightarrow L^2 + p = 4kt \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cbegin%7Baligned%7DL%20%3D%20%5Csqrt%7B4kt%20-%20p%7D%20%26%20%5Crightarrow%20L%5E2%20%3D%20%5Cbig%28%20%5Csqrt%7B4kt%20-%20p%7D%20%5Cbig%29%20%5E2%20%5C%5C%26%20%5Crightarrow%20L%5E2%20%3D%204kt%20-%20p%20%5C%5C%26%20%5Crightarrow%20L%5E2%20%2B%20p%20%3D%204kt%20%5C%5C%5Cend%7Baligned%7D)
Next, <em>divide 4t by both sides</em>:
![\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\& \rightarrow L^2 + p = 4kt \\& \rightarrow \frac{L^2 + p}{4t} = k \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cbegin%7Baligned%7DL%20%3D%20%5Csqrt%7B4kt%20-%20p%7D%20%26%20%5Crightarrow%20L%5E2%20%3D%20%5Cbig%28%20%5Csqrt%7B4kt%20-%20p%7D%20%5Cbig%29%20%5E2%20%5C%5C%26%20%5Crightarrow%20L%5E2%20%3D%204kt%20-%20p%20%5C%5C%26%20%5Crightarrow%20L%5E2%20%2B%20p%20%3D%204kt%20%5C%5C%26%20%5Crightarrow%20%5Cfrac%7BL%5E2%20%2B%20p%7D%7B4t%7D%20%3D%20k%20%5C%5C%5Cend%7Baligned%7D)
We can rewrite the new equation by swapping sides to obtain our final expression:
![\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow \boxed{k = \frac{L^2 + p}{4t}}\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cbegin%7Baligned%7DL%20%3D%20%5Csqrt%7B4kt%20-%20p%7D%20%26%20%5Crightarrow%20%5Cboxed%7Bk%20%3D%20%5Cfrac%7BL%5E2%20%2B%20p%7D%7B4t%7D%7D%5Cend%7Baligned%7D)
∴ we have <em>changed</em> the subject of the formula.
---
Learn more about Algebra I: brainly.com/question/27698547
---
Topic: Algebra I